2022
DOI: 10.1097/corr.0000000000002265
|View full text |Cite
|
Sign up to set email alerts
|

Impact of First Metatarsal Hyperpronation on First Ray Alignment: A Study in Cadavers

Abstract: BackgroundThere is increased evidence of first metatarsal hyperpronation in patients with hallux valgus, but its impact on the stability of the first metatarsophalangeal and metatarsosesamoid joints is unknown. A previous biomechanical study showed that an increase in hallucal pronation might lead to medial soft tissue failure of the first metatarsophalangeal joint. Conversely, dynamic studies on hallux valgus have shown that the first tarsometatarsal joint moves in supination during weightbearing, and supinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…As Lalevée et al [1] noted in the current study in cadavers, the combination of first metatarsal intrinsic hyperpronation and first metatarsophalangeal medial soft tissue failure led to a hallux valgus deformity. The authors indicated that hallux valgus is a dynamic condition, and the deformity could be more correlated with motions during weightbearing than with plain static measurements.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…As Lalevée et al [1] noted in the current study in cadavers, the combination of first metatarsal intrinsic hyperpronation and first metatarsophalangeal medial soft tissue failure led to a hallux valgus deformity. The authors indicated that hallux valgus is a dynamic condition, and the deformity could be more correlated with motions during weightbearing than with plain static measurements.…”
supporting
confidence: 65%
“…To further evaluate how medial deviation and/or hyperpronation of the first metatarsal affects the stability of the first metatarsophalangeal and metatarsosesamoid joints, a cadaver model could be tested, similar to what Lalevée et al [1] did in the current study. This also could be tested in a biomechanical model.…”
Section: How Do We Get There?mentioning
confidence: 99%
“…The high recurrence rates in the long term for all categories of surgical procedures suggest that better understanding of pathogenesis and prognosis of HV is required to prescribe the ideal treatment, before modifying or introducing new surgical techniques. 21,28…”
Section: Discussionmentioning
confidence: 99%
“…The proximal tibia was then potted in a square block using polymethylmethacrylate bone cement. The cemented block was utilized to fix the specimen vertically and in a plantigrade fashion into an external radiolucent frame that was previously utilized in the literature to allow for simulated weight bearing (17) . Weight bearing was simulated by introducing 36.3 kilograms (356N) of vertical load into the specimen frame construct (Figure 1).…”
Section: Specimen Preparation and External Framementioning
confidence: 99%